Petrol price regulation in South Africa: Is it meeting its intended objectives? - Rod Crompton; Midesh Sing; Vernon Filter; Nonhlanhla Msimango (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The South African liquid fuels industry is a significant part of the economy. Historically, government policy focused on import substitution industrialization to support industry margins. This approach is called into question by the 2006 shift from net exports to imports and by inflated downstream regulated margins. This study focuses on the regulated petrol price. Import parity pricing regulation has not kept pace with market changes. A policy shift in 1998 towards marketrelated pricing has not materialized. Instead, regulated margins have increased over the last 20 years in real terms, partly attributable to methodological errors in the regulatory accounting system. The long-term excess of service stations persists despite declining petrol and diesel volumes between 2005 and 2019. Estimates suggest that the petrol price could be lower by 0.70-0.80 rands/litre. Price deregulation is inhibited by political regulation and social policies entangled in regulation.
Keywords: K23; L59; D04; D40; 330; petrol price; South Africa; deregulation; regulatory accounting system